Designing Strategy to Increase Intention to Use Maternal Perinatal Death Notification (MPDN) Technology in North Sumatra - Pandiangan, Deo Pratama; Erlinda Muslim (Jurnal Sistem Teknik Industri, 2022)
In order to reduce the Maternal Mortality Rate (MMR) in Indonesia, the government has made various innovations to lessen the MMR. One of the improvement is to put in force Maternal Perinatal Death Notification (MPDN) technology. But in the implementation, there are still many hospitals and health centers in North Sumatra that have not longer applied MPDN optimally. Considering that North Sumatra is one of the provinces with the very best MMR in Indonesia, the utilization of MPDN desires to be extended in North Sumatera. In preceding research, it became stated that the readiness and recognition of a technology will have an affect on the successful implementation of the technology. Therefore, this take a look at pursuits to measure and notice the effect of every variable at the acceptance of MPDN technology based on the Unified Theory of Acceptance and Use of Technology (UTAUT). The variables located to have an influence at the acceptance of MPDN technology in North Sumatra are overall performance expectancy, effort expectancy, social influence, self-efficacy and technology anxiety. These five influential variables are then used as the basis for building strategies using Importance- Performance Analysis (IPA).